Determination of the Rotation Curve of the Milky Way Using the 21 cm Hi Emission Line - Mahdi, H. S.; Mohsin, D. S. (Iraqi Journal of Science, 2022)
In this paper, the rotation curve of the Milky Way galaxy has been determined using the observed HI emission line at a wavelength of 21 cm. Particularly, the Tangent Point Method was used in order to measure the rotational velocity and the distance to the center of the Milky Way. The measured rotation curve showed that the rotational velocity remains approximately constant at large distances from the center of the Galaxy. This is actually an evidence for the existence of dark matter in the halo of the Milky Way. If all the matter in the Milky Way is visible, then the behavior of the rotation curve of the galaxy should experience a Keplerian decline. The mass of the Milky Way within a radius of 15 kpc was also estimated to be 1.65 × 1011 M⊙ which represents the mass of luminous matter in the Galaxy. However, if one assumes that the dark matter halo extends to 50 kpc, then the mass of the Galaxy should be 5.615 × 1011 M⊙. The results indicate that the mass of dark matter in the Milky way within a radius of 50 kpc is 3.96 × 1011 M⊙.